(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The present work had the purpose of defining the category of "political romanticism" developed by the German philosopher Carl Schmitt, applying its meaning of "romantic politics" to the case of the Chilean political poet Guillermo Matta Goyenechea (1829-1889). Through the terms stories such as imagination, cosmic language, moral progress, democracy, among others, this poet-politician articulated his social discourse during the period from 1853 to 1858, as elements of dispute with the ruling power under the intention of reforming the chilean society of his time.